Peningkatan Kesadaran dan Pencegahan Perilaku Bullying Melalui Sosialisasi Pada Anak Sekolah Dasar di Daerah Pedesaan - Mauliana; Yodha Pasaribu; Firya Faiza; Amanda Riza; Elly Susanti; Suci Fajarni; Riki Yulianda (Dedikasi Sosial: Jurnal Pengabdian Masyarakat, 2025)
Abstract. The incidence of bullying among elementary school students has become increasingly alarming. The consequences of bullying are multifaceted, encompassing psychological, sociological, and other detrimental effects. Consequently, there is a pressing need for comprehensive educational interventions to equip students with the knowledge and skills to prevent bullying. This community service project aimed to deliver an extensive educational program on bullying behavior to sixth-grade students at SD Tanjung Selamat, a primary school situated in a rural area. The methodology employed involved interactive communication and role-playing techniques, implemented through three stages: (1) material presentation, (2) interactive questioning, and (3) evaluation. Findings indicate a considerable deficiency in students’ understanding of the various forms, impacts, and identification of bullying prior to the intervention. Following the program, participants exhibited enhanced awareness and recognition of bullying behaviors. Moreover, the initiative sought to sensitize perpetrators to the consequences of their actions, thereby discouraging future occurrences. It is anticipated that this educational effort will promote more responsible student conduct and contribute to fostering a safe and bully-free school environment. Additionally, structural preventative measures involving educators and school committees are recommended to mitigate the recurrence of bullying incidents